Pemberdayaan Masyarakat dalam Penelusuran Sejarah Desa Pangadegan Kecamatan Pagelaran - Muhammad Toha; Ika Rustika Zainah; Alfa Rohmatin; Sri Zulfa Laeliyah Bilqis Tadzkir Putri; Denda Juanda; Ahmad Pahmi Alhusaeni; Muhammad Nasihudin (Lembaga Pengembangan Kinerja Dosen, 2025)
Village history is an important identity that needs to be preserved to prevent it from being lost over time. Pangadegan Village in Pagelaran District, South Cianjur, has a historical legacy that has not been scientifically documented and is at risk of being forgotten by the younger generation. This community service activity aims to explore and document the local history of Pangadegan Village by involving active community participation as a form of empowerment. The approach used is the Asset-Based Community Development method, which focuses on exploring historical assets and local potential through the stages of identification, deliberation, design, agreement, and sustainable development. The activity was implemented through in-depth interviews with village elders, observations of historical sites, focus group discussions, and documentation training for youth. The results of the activity indicate increased community awareness of the importance of village history, the establishment of an initiative to form a village archives team, and the creation of documentation products in the form of small books and digital publications. This activity also opens up opportunities for the development of history-based cultural and educational tourism as a form of sustainability. Thus, this community service activity confirms that preserving local history through an asset-based approach can strengthen identity, empower communities, and provide sustainable social, cultural, and economic benefits.